The Influence of Brand Ambassadors in Building Brand Image and Their Impact on Purchasing Decisions for Scarlett Whitening Products - Arief, Alya Luthfiyyah; Puspasari, Tri Ratih; Stellarosa, Yolanda (GoAcademica Research & Publishing, 2024)
The Indonesian cosmetic industry is experiencing significant growth, driven by high consumer demand and an expanding market. This burgeoning industry has attracted several Indonesian celebrities to venture into the cosmetic business. The advancement of technology has subtly transformed the lifestyle of society, especially with the advent of social networks, which have provided business players with numerous marketing strategies that capture public attention. One such strategy is the use of brand ambassadors, who have become increasingly prominent in helping businesses introduce their products. The aim of this research is to understand the impact of brand ambassadors on building brand image and their subsequent effect on purchasing decisions of Scarlett Whitening products. This study utilizes the Elaboration Likelihood Model theory and employs a descriptive quantitative method. The population of the study consists of women aged 18-28 who use Scarlett Whitening products and follow the Instagram account @scarlett_whitening, totaling 100 respondents. The analysis techniques employed in the study include instrument testing, descriptive analysis, classical assumption testing, multiple regression analysis, correlation testing, and the Sobel test. The findings of the research reveal a positive and significant influence of brand ambassadors on both brand image and the purchasing decisions of Scarlett Whitening products. The researcher hopes that Scarlett Whitening will consider this study as a valuable reference in selecting brand ambassadors with similar criteria to enhance their brand image and its impacts. By strategically choosing brand ambassadors who resonate well with the target audience, Scarlett Whitening can strengthen its market position and drive consumer purchase decisions more effectively.